AMSSM Position Statement Update: Blood-Borne Pathogens in the Context of Sports Participation. Issue 4 (July 2020) - McGrew, Christopher; MacCallum, Daisy-Scarlett; Narducci, Dustymarie; Nuti, Rathna; Calabrese, Leonard; Dimeff, Robert; Paul, Stephen; Poddar, Sourav K.; Rao, Ashwin; McKeag, Douglas
Abstract : Abstract: This AMSSM position statement update is directed toward health care providers of patients involved in sport and exercise. There have been significant advances in clinical and scientific research in the understanding of blood-borne pathogens (BBPs), and this update incorporates these advancements. This document is intended as a general guide to clinical practice based on the current state of evidence, while acknowledging the need for modification as new knowledge becomes available. Confirmed transmission of BBPs during sport is exceedingly rare. There are no well-documented reports of HIV, hepatitis C virus, or hepatitis D virus transmission during sport. There is also no evidence for universal testing for BBPs as a specific requirement for participation in sports. Competitive athletes and nonathletes should follow appropriate general public health agency recommendations for screening for BBPs, considering their individual risk factors and exposures. Standard (universal) precautions must be followed by those providing care to athletes. Exercise and athletic participation can help promote a healthy lifestyle for persons living with BBPs. Those with acute symptomatic BBP infection should limit exercise intensity based on their current health status. Education is the key tool for preventing BBP transmission. Research gaps include evaluation of the prevalence of BBP infections in competitive athletes, the effects of long-term, intense training on infected athletes, and the effects of BBP treatment therapies on performance.